Effect of narrowband ultraviolet B phototherapy on melanocytic naevi. (27th February 2013) - Lin, C.Y.; Oakley, A.; Rademaker, M.; Hill, S.; Yung, A.
Summary Background Melanocytic naevi have been observed to undergo morphological changes following exposure to narrowband ultraviolet (NB‐UV)B radiation. Objectives To analyse changes in naevi exposed to NB‐UVB in a large cohort of patients. Methods Subjects referred for phototherapy had macroscopic and dermoscopic images taken of prominent melanocytic naevi at the following time points: immediately prior to NB‐UVB treatment, after 10 exposures, after 30 exposures or at the end of treatment if earlier, and 3 months after discontinuing treatment. Four dermatologists, by consensus, examined each naevus for specific clinical and dermoscopic features at each time point. The size (area) of each naevus was determined by plenimetry. Results Complete sets of images were taken for 36 out of 51 patients. The most common global dermoscopic patterns in the 440 naevi examined were reticular (50%) and globular (32%). Following NB‐UVB exposure, blurring or merging of lines was observed in 45% of reticular naevi. An increase in colour intensity and in the number of dots or globules was observed in 63% of globular naevi, and 167 naevi (40%) underwent a change in size. Of these, 91/167 (54%) decreased in size, with a median area reduction of 8% (0·9–42%); while 76/167 (46%) increased in size, with a median area increase of 9% (1–76%). Conclusions Around half of naevi exposed to a course of NB‐UVB treatment undergo size or morphological changes. Naevi that enlarged tended to revert to pretreatment size 3 months after discontinuation of phototherapy.